2020
DOI: 10.21203/rs.3.rs-62218/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety and Feasibility of Umbilical Cord Mesenchymal Stem Cells in Patients with COVID-19 Pneumonia: A Pilot Study

Abstract: Background: We aim to explore the safety and feasibility of umbilical cord mesenchymal stem cells (UC-MSCs) transplantation in severe and critically severe type Coronavirus disease 2019 (COVID-19) patients.Methods: In addition to normal therapy, we performed four times transplantation of UC-MSCs in 16 severe and critically severe type COVID-19 patients. We observed adverse events from enrollment to D28. We evaluated the oxygenation index, inflammatory biomarkers, chest imaging, lymphocyte subsets count et al o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Safety was shown in other studies that also performed MSC-based interventions. They did not noticed any acute infusion-related issues, alergic reaction, delayed hypersensitivity or secondary infections in the patients either 39,45,47,48,54,76,77 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Safety was shown in other studies that also performed MSC-based interventions. They did not noticed any acute infusion-related issues, alergic reaction, delayed hypersensitivity or secondary infections in the patients either 39,45,47,48,54,76,77 .…”
Section: Discussionmentioning
confidence: 87%
“…Studies have shown that intravenous MSC infusion in patients with COVID-19 is safe and welltolerated. It prevents or reduces ARDS and other serious complications, decreases in ammatory cytokines and mortality, and in some cases improves pulmonary 39,[44][45][46][47][48][49][50][51][52][53][54][55][56] . Therapeutic interventions must decrease excess in ammation, thus preventing end-organ damage and long-term functional disability in moderate or severe COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, mesenchymal stem cells which was investigated extensively in recent years might be an eligible candidate. [8][9][10][11] In the entire course of his illness, the serum IL-6 (62 pg/mL), ferritin (1.21 g/L), and LDH (780 U/L) only had a slight elevation in the early period, there is no typical cytokine storm as that was seen in non-COVID-19 ARDS. The COVID-19 associated thrombosis has been noticed by many clinicians, 12,13 heparin was regularly used to prevent thrombosis even after the patient was weaned from ECMO.…”
Section: Discussionmentioning
confidence: 90%
“…Of the 25 included studies, we included 3 RCTs, 37,44,45 5 comparative observational studies, [46][47][48][49][50] and 17 case-series/case reports. [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] The studies were conducted in seven countries, including Asia (n=16), Europe (n=6), North America (n=2), and South America (n=1).…”
Section: Resultsmentioning
confidence: 99%